"Marginal keratitis following COVID 19 vaccination". (2022) - Farrell, Daniel A.; Deacon, Sara; Mauger, Thomas
Abstract: Purpose: To describe a novel case of marginal keratitis following COVID 19 vaccination. Methods: Case report Results: A 68-year-old female received the Moderna COVID 19 vaccine. She then developed ocular irritation and peripheral corneal opacities that are characteristic of marginal keratitis. Her symptoms responded well to steroid and antibiotic ophthalmic medications. She received her second dose of the Moderna vaccine while still taking her eye drops and was then able to taper off her drops without a recurrence of symptoms. Conclusions: Marginal keratitis represents a localized type III hypersensitivity reaction of the cornea. The SARS-CoV-2 virus that causes COVID 19 gains entry into the cell via binding of the spike protein with the ACE2 receptor. It is this spike protein that is the target for mRNA COVID-19 vaccines, such as the Moderna vaccine, allowing spike protein antigen recognition by the human immune system. The cornea has been found to have significant levels of ACE2 receptors, potentially allowing for the cornea to become a site for the antigen-antibody complex deposition necessary for a type III hypersensitivity response. This reaction should be recognized so that treatment may be provided during the initial episode and the cornea may be monitored following subsequent vaccinations.